The Influence of Free Cash Flow, Profit Stability, Level of Asset Expansion, Leverage, and Company Funding Requirements on Dividend Policy - Patonah, Dedeh Siti; Wiharno, Herma; Nurhandika, Arief (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2023)
This study aims to analyze the effect of free , earnings stability, level of asset expansion, , and the company's funding requirements on dividend policy partially and simultaneously empirical studies on industrial sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2017 period 2021. The data used is secondary data obtained using non- participating observation techniques. The method used in this research is descriptive and verification method with a quantitative approach. Samples were taken using quota sampling, and 26 companies were obtained. The analysis technique used is panel data regression analysis. Data processing uses the eviews 9.0 program. This study uses the variables free , earnings stability which is proxied by SM, the level of expansion of assets which is proxied by GROWTH, is proxied by DER, and the company's funding requirements are proxied by CR. The results shows that simultaneously free , the stability of company earnings, the level of expansion of assets, , and the company's funding requirements have a significant positive effect on dividends policy. Partially, free has a significant positive effect on dividends policies, earnings stability has a significant positive effect on dividend policy, the level of asset expansion has no significant negative effect on dividend policy, has no significant negative effect on dividends policies, and the company's funds requirements have a significant positive effect on dividends policy. From this study, the adjusted R-square value was 0.2244693, which means that 22.45% of the change in the dependent variables can be explained by the determining variables in the model, while the remaining 77.55% is influenced by other variables studied.